17.4k views
3 votes
If you expand and simplify (2x+3)(x+4)

2 Answers

3 votes


(2x + 3)(x + 4) \\ = 2x(x + 4) + 3(x + 4) \\ = 2x * x + 2x * 4 + 3 * x + 3 * 4 \\ = {2x}^(2) + 8x + 3x + 12 \\ = {2x}^(2) + 11x + 12 \\ hope \: it \: helps

User Azibom
by
5.0k points
6 votes

Answer:

The answer is 2x² + 11x + 12.

Explanation:

You have apply Distributive Law,


a(m + n) = am + an

So for this question :


(2x + 3)(x + 4)


= 2x(x) + 2x(4) + 3(x) + 3(4)


= 2 {x}^(2) + 8x + 3x + 12


= 2 {x}^(2) + 11x + 12

User Steharro
by
5.2k points